Application and mechanism of anti-VEGF drugs in age-related macular degeneration - Song, Dawei; Liu, Ping; Shang, Kai; Ma, YiBin (Frontiers in Bioengineering and Biotechnology, 2022)
Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly. With the advent of China's aging society, the number of patients is increasing year by year. Although researchers have done a lot of basic research and clinical research on the pathogenesis and treatment of AMD in recent years, the pathogenesis of AMD is still controversialdue to the complexity of the disease itself. AMD is the primary cause of blindness in the elderly over 50 years old. It is characterized by the formation of choroidal neovascularization (CNV) and the over secretion of vascular endothelial growth factor (VEGF) as its main mechanism, which can eventually lead to vision loss or blindness.Targeted VEGF drugs for neovascularization, such as Lucentis and Aflibercept, are the first-line drugs for AMD. Their application has greatly reduced the blinding rate of patients. However, there are still some patients who have no response to treatment or cannot maintain their vision after long-term treatment.Frequent injection also increases the risk of complications and economic burden. In order to further improve the quality of life and long-term prognosis of AMD patients, a variety of new treatmentshave been or will be applied in clinic, including combined treatment with the same or different targets to improve the curative effect, change or simplify the mode of medication, inhibit VEGF receptor tyrosine protein kinase and so on. This article provides a brief review of the research progress of anti-VEGF drugs and their mechanisms for the treatment of AMD